The Golden ratio! 2

Algebra Level 3

If ϕ = 1 + 5 2 \phi = \dfrac{1+\sqrt5}2 , compute 1 ϕ + 1 ϕ 3 + 1 ϕ 5 + 1 ϕ 7 + \dfrac1\phi + \dfrac1{\phi^3}+ \dfrac1{\phi^5}+ \dfrac1{\phi^7} + \cdots .

1 ϕ 2 \frac \phi2 ϕ \phi ϕ 2 \phi ^2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mateus Gomes
Feb 6, 2016

For a geometric progression with initial term a a and common ratio r r satisfying r < 1 , |r|<1, the sum of the infinite terms of the geometric progression is S = a 1 r S_{\infty}=\frac{a}{1-r} a = 1 ϕ , r = 1 ϕ 2 \rightarrow a=\frac{1}{\phi}, r=\frac{1}{{\phi}^2} 1 ϕ 1 1 ϕ 2 = 1 ϕ ϕ 2 1 ϕ 2 = ϕ ϕ 2 1 = ϕ ( ϕ 1 ) ( ϕ + 1 ) = 1 + 5 2 ( 1 + 5 2 1 ) ( 1 + 5 2 + 1 ) = 1 + 5 2 ( 5 1 2 ) ( 5 + 3 2 ) = ( 1 + 5 2 ) × ( 2 5 1 ) × ( 2 5 + 3 ) = ( 2 + 2 5 2 + 2 5 ) = 1 \rightarrow\frac{\frac{1}{\phi}}{1-\frac{1}{\phi^2}}=\frac{\frac{1}{\phi}}{\frac{{\phi}^{2}-1}{{\phi}^{2}}}=\frac{\phi}{{\phi}^{2}-1}=\frac{\phi}{(\phi-1)(\phi+1)}=\frac{\frac{1+\sqrt5}{2}}{(\frac{1+\sqrt5}{2}-1)(\frac{1+\sqrt5}{2}+1)}=\frac{\frac{1+\sqrt5}{2}}{(\frac{\sqrt5-1}{2})(\frac{\sqrt5+3}{2})}=(\frac{1+\sqrt5}{2})\times(\frac{2}{\sqrt5-1})\times(\frac{2}{\sqrt5+3})=(\frac{2+2\sqrt5}{2+2\sqrt5})=\Large\color{#3D99F6}{\boxed{1}}

Nice(+1)..Did the same way.... But instead of putting values of ϕ \phi you could have used the fact that ϕ 2 ϕ 1 = 0 \phi^2-\phi-1=0 or ϕ = ϕ 2 1 \phi=\phi^2-1 or ϕ ϕ 2 1 = 1 \dfrac{\phi}{\phi^2-1}=1

Rishabh Jain - 5 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...